Answer:
-8.21
Step-by-step explanation:
Answer:
![L(x)=1+\dfrac{1}{3}x](https://tex.z-dn.net/?f=L%28x%29%3D1%2B%5Cdfrac%7B1%7D%7B3%7Dx)
![\sqrt[3]{0.95} \approx 0.9833](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B0.95%7D%20%5Capprox%200.9833)
![\sqrt[3]{1.1} \approx 1.0333](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B1.1%7D%20%5Capprox%201.0333)
Step-by-step explanation:
Given the function: ![g(x)=\sqrt[3]{1+x}](https://tex.z-dn.net/?f=g%28x%29%3D%5Csqrt%5B3%5D%7B1%2Bx%7D)
We are to determine the linear approximation of the function g(x) at a = 0.
Linear Approximating Polynomial,![L(x)=f(a)+f'(a)(x-a)](https://tex.z-dn.net/?f=L%28x%29%3Df%28a%29%2Bf%27%28a%29%28x-a%29)
a=0
![g(0)=\sqrt[3]{1+0}=1](https://tex.z-dn.net/?f=g%280%29%3D%5Csqrt%5B3%5D%7B1%2B0%7D%3D1)
![g'(x)=\frac{1}{3}(1+x)^{-2/3} \\g'(0)=\frac{1}{3}(1+0)^{-2/3}=\frac{1}{3}](https://tex.z-dn.net/?f=g%27%28x%29%3D%5Cfrac%7B1%7D%7B3%7D%281%2Bx%29%5E%7B-2%2F3%7D%20%5C%5Cg%27%280%29%3D%5Cfrac%7B1%7D%7B3%7D%281%2B0%29%5E%7B-2%2F3%7D%3D%5Cfrac%7B1%7D%7B3%7D)
Therefore:
![L(x)=1+\frac{1}{3}(x-0)\\\\$The linear approximating polynomial of g(x) is:$\\\\L(x)=1+\dfrac{1}{3}x](https://tex.z-dn.net/?f=L%28x%29%3D1%2B%5Cfrac%7B1%7D%7B3%7D%28x-0%29%5C%5C%5C%5C%24The%20linear%20approximating%20polynomial%20of%20g%28x%29%20is%3A%24%5C%5C%5C%5CL%28x%29%3D1%2B%5Cdfrac%7B1%7D%7B3%7Dx)
(b)![\sqrt[3]{0.95}= \sqrt[3]{1-0.05}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B0.95%7D%3D%20%5Csqrt%5B3%5D%7B1-0.05%7D)
When x = - 0.05
![L(-0.05)=1+\dfrac{1}{3}(-0.05)=0.9833](https://tex.z-dn.net/?f=L%28-0.05%29%3D1%2B%5Cdfrac%7B1%7D%7B3%7D%28-0.05%29%3D0.9833)
![\sqrt[3]{0.95} \approx 0.9833](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B0.95%7D%20%5Capprox%200.9833)
(c)
(b)![\sqrt[3]{1.1}= \sqrt[3]{1+0.1}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B1.1%7D%3D%20%5Csqrt%5B3%5D%7B1%2B0.1%7D)
When x = 0.1
![L(1.1)=1+\dfrac{1}{3}(0.1)=1.0333](https://tex.z-dn.net/?f=L%281.1%29%3D1%2B%5Cdfrac%7B1%7D%7B3%7D%280.1%29%3D1.0333)
![\sqrt[3]{1.1} \approx 1.0333](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B1.1%7D%20%5Capprox%201.0333)
Step-by-step explanation:
![\frac{1}{4} \boxed{?} \frac{3}{8} \\ \\ \frac{1}{4} = \frac{2}{8} \\ \\ \because \: 2 < 3 \\ \therefore \: \frac{1}{4} \boxed{ < } \frac{3}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B4%7D%20%20%5Cboxed%7B%3F%7D%20%5Cfrac%7B3%7D%7B8%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cfrac%7B1%7D%7B4%7D%20%20%3D%20%20%5Cfrac%7B2%7D%7B8%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Cbecause%20%5C%3A%202%20%3C%203%20%5C%5C%20%20%5Ctherefore%20%5C%3A%20%20%5Cfrac%7B1%7D%7B4%7D%20%20%5Cboxed%7B%20%3C%20%7D%20%5Cfrac%7B3%7D%7B8%7D%20)
Answer:
gog(x)=9x-16
Step-by-step explanation:
We are given g(x)=3x-4 and are asked to find (gog) (x)
gog(x)=g(g(x))
g(x)=3x-4
Hence
g(g(x))=g(3x-4)
=3(3x-4)-4
=9x-12-4
=9x-16
Hence
gog(x)=9x-16
Answer:
C
Step-by-step explanation: